Olfactory Proteins and Their Expression Profiles in the Eucalyptus Pest Endoclita signifier Larvae - Zhang, Xiaoyu; Yang, Zhende; Yang, Xiuhao; Ma, Hongxuan; Liu, Xiumei; Hu, Ping (Frontiers in Physiology, 2021)
The new wood-boring pest Endoclita signifer is the polyphagous insect, but it damages exotic eucalyptus universally and severely after plantation it in south of China from 2007, which is the typical example that native insect adaptation to the exotic host. Interestingly the larvae transfer themselves from soil to standing tree, then damage it with wormhole and package after the third instar. Although female oviposition dispersed, larvae can damage eucalyptus in mingled forest with eight species accurately, so we hypothesized larvae olfactory contribution to its host selection. The transcriptome of head and tegument and expression profile of olfactory proteins of E. signifier larvae were investigated. Results showed that 15 odorant binding proteins, six chemosensory proteins, two odorant receptors, one gustatory receptor, 14 ionotropic receptors and one sensory neuron membrane protein were identified. Expression profiles indicated that all of the tested olfactory proteins, except for EsigCSP1, could be expressed in larvae head, whereas almost all of the genes were also detected in non-olfactory tissues, especially in thorax tegument. Further, EsigOBP2, EsigOBP8, EsigGOBP1, EsigGOBP2, EsigGOBP5, EsigCSP3, EsigCSP5, and EsigOR1 were expressed most strongly in the head, furthermore EsigCSP3 was only expressed in the head with a substantial quantity and EsigGOBP2, EsigCSP5, and EsigOR1 exhibited biased expression. EsigGR1 exhibited the highest expression among all tissues. Besides phylogenetic analysis shows that EsigGOBP7 probably is the PBP of E. signifier. This work establishes the foundation for the study of chemosensation in the E. signifier larvae, suggesting further studies to explore specific olfactory genes, such as EsigCSP3 and EsigGR1, which underlie the ecologically relevant behaviours of larvae.